2005
DOI: 10.1300/j039v09n01_03
|View full text |Cite
|
Sign up to set email alerts
|

Social Workers' Attitudes Toward Parents of Children in Child Protective Services: Evaluation of a Family-Focused Casework Training Program

Abstract: Recent concerns regarding permanence for foster children have inspired child welfare agencies to re-focus more of their efforts on biological parents as permanent resources for children in care. The social work field has responded to this situation with family-focused training for frontline staff; one such curriculum is the Family Development Credential (FDC). Tools exist for evaluating FDC trainees' retention of material and ability to integrate FDC concepts into practice. However, the transformative nature o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 20 publications
0
23
0
Order By: Relevance
“…In two studies (Alpert and Britner 2005;Bibus 1993) no effects of the training were found; both were studies that utilized post-test only designs and secondary data analysis. Alpert and Britner (2005) reported on a training program that was designed to influence caseworkers to be more family-focused in their attitudes.…”
Section: No Effectiveness Of Trainingmentioning
confidence: 99%
See 4 more Smart Citations
“…In two studies (Alpert and Britner 2005;Bibus 1993) no effects of the training were found; both were studies that utilized post-test only designs and secondary data analysis. Alpert and Britner (2005) reported on a training program that was designed to influence caseworkers to be more family-focused in their attitudes.…”
Section: No Effectiveness Of Trainingmentioning
confidence: 99%
“…Most (n = 9) focused on a highly specific content area or population group such as work with involuntary clients (Bibus 1993;Bibus and Rooney 1995), Indian child welfare practice (Bending 1997), investigative interviewing (Freeman and Morris 1999), domestic violence (Saunders and Anderson 2000;Mills and Yoshihama 2002), interagency collaboration (Jones et al 2002), leading multidisciplinary teams (Zimmerman et al 2003), and family-focused practice (Alpert and Britner 2005). The others (n = 5) were more general, such as those focusing on entry-level casework practice (Cheung et al 1991;Leung and Cheung 1998); (Strand and Badger 2005); child abuse and neglect (Smith et al 2000); and various types of substantive content (e.g., Owens-Kane et al 2005).…”
Section: Training Interventionmentioning
confidence: 99%
See 3 more Smart Citations